2012
DOI: 10.1016/s1470-2045(11)70404-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between endometriosis and risk of histological subtypes of ovarian cancer: a pooled analysis of case–control studies

Abstract: SummaryBackgroundEndometriosis is a risk factor for epithelial ovarian cancer; however, whether this risk extends to all invasive histological subtypes or borderline tumours is not clear. We undertook an international collaborative study to assess the association between endometriosis and histological subtypes of ovarian cancer.MethodsData from 13 ovarian cancer case–control studies, which were part of the Ovarian Cancer Association Consortium, were pooled and logistic regression analyses were undertaken to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
598
6
28

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 800 publications
(679 citation statements)
references
References 43 publications
22
598
6
28
Order By: Relevance
“…As such, endometriosis should also be recognized as an indication for FPT: patients with endometriosis-related symptoms, like pelvic pain or the presence of ovarian cysts, frequently undergo extensive pelvic surgery involving the ovaries [9]. The need for surgery and histological evaluation is also justified by recent studies indicating an increased risk for malignancy in patients suffering from endometriosis when large or rapidly growing endometriomas are detected or when suspicious changes in sonographic appearance occur [10].…”
Section: Introductionmentioning
confidence: 99%
“…As such, endometriosis should also be recognized as an indication for FPT: patients with endometriosis-related symptoms, like pelvic pain or the presence of ovarian cysts, frequently undergo extensive pelvic surgery involving the ovaries [9]. The need for surgery and histological evaluation is also justified by recent studies indicating an increased risk for malignancy in patients suffering from endometriosis when large or rapidly growing endometriomas are detected or when suspicious changes in sonographic appearance occur [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian clear cell adenocarcinoma is often associated with endometriosis, 18,19 and we have recently shown that stress caused by excess iron leads to amplification of the Met gene and carcinogenesis in the ovary. 20,21 Compared with serous adenocarcinoma, clear cell adenocarcinoma is resistant to standard platinum-based chemotherapy; 22 thus, survival rates in patients with advanced stages of ovarian clear cell adenocarcinoma are poor.…”
mentioning
confidence: 99%
“…Пограничные серомуцинозные опухоли ранее отно-сились к эндоцервикальному варианту пограничных му-цинозных опухолей яичника, сейчас вместе с эндоме-триоидными карциномами и светлоклеточными карци-номами составляют группу «опухолей, развивающихся из эндометриоза» [11]. Важнейшим звеном патогенеза этих новообразований является инактивирующая мута-ция ARID1А -гена-супрессора опухолевого роста, ко-дирующего белок BAF250a комплекса SWI-SNF-A, уча-ствующего в ремоделировании хроматина [12].…”
Section: архив патологии 4 2015unclassified